2021
DOI: 10.1021/acscatal.1c04427
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneous Enantioselective Hydrogenation of Ketones by 2-Amino-2′-hydroxy-1,1′-binaphthyl-Modified CeO2-Supported Ir Nanoclusters

Abstract: Modification of supported noble metals with chiral modifiers is a promising strategy for the design of effective heterogeneous chiral catalysts. The chiral compounds are generally introduced on the surface of noble metals, often leading to low enantioselectivity and to low activity. Herein, a unique heterogeneous chiral catalyst where a chiral modifier is introduced at the interface between the metal cluster and the support is presented. Modification of CeO2-supported Ir nanoclusters with 2-amino-2′-hydroxy-1,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 70 publications
0
2
0
1
Order By: Relevance
“…From X-ray absorption near edge structure (XANES) spectroscopy (Figure a), the white line intensity of Ir SL /CeO 2 is situated above that of Ir foil and slightly lower than that of IrO 2 , indicating the positively charged Ir δ+ species. X-ray photoelectron spectroscopy (XPS) spectra show that the valences of Ir NP contain 0 and +4, while the valence of Ir SAC is +4 only (Figure S11). , The oxidation state of Ir SL is between that of Ir NP and Ir SAC , with valences of +3 and +4.…”
Section: Results and Discussionmentioning
confidence: 99%
“…From X-ray absorption near edge structure (XANES) spectroscopy (Figure a), the white line intensity of Ir SL /CeO 2 is situated above that of Ir foil and slightly lower than that of IrO 2 , indicating the positively charged Ir δ+ species. X-ray photoelectron spectroscopy (XPS) spectra show that the valences of Ir NP contain 0 and +4, while the valence of Ir SAC is +4 only (Figure S11). , The oxidation state of Ir SL is between that of Ir NP and Ir SAC , with valences of +3 and +4.…”
Section: Results and Discussionmentioning
confidence: 99%
“…Soni 等 [94] 在 l-脯氨酸的存在下由共沉淀法合成了手 , c) Au@SAM/MCF-17 催化的分子间环丙烷化和分子内环丙烷化反应 [35] 、(d) CeO 2 负载催化剂上苯乙酮的不对称加氢反应和(e, f) (R)-NOBIN 在氧化 铈负载的铱纳米团簇上的吸附、苯乙酮在多相手性催化剂上的吸附和对映选择性机理示意图 [93] Figure 9 (a) Preparation of Au nanoclusters encapsulated in chiral SAM/mesoporous MCF-17 support and chemical structures of five chiral molecules for SAM, (b, c) Au@SAM/MCF-17 catalyzed intermolecular cyclopropane synthesis and intramolecular cyclopropane synthesis [35] , (d) hydrogenation of acetophenone over CeO 2 -supported catalysts, and (e, f) schematic diagram of adsorption of (R)-NOBIN on Ir 10 /CeO 2 , adsorption and enantioselectivity of acetophenone on heterogeneous chiral catalysts [93] 图 10 l-脯氨酸修饰的 ZnS 量子点催化不对称羟醛缩合反应的反应机 理 [94] Figure 10 Reaction mechanism of asymmetric Aldol condensation catalyzed by l-proline modified ZnS quantum dots [94] 位羟基形成氢键的过程有关. 此外根据不同芳香醛的反 应, 发现其中的芳环对反应物的空间和电子取向都起到 重要作用, 并且能够稳定过渡态, 使产物具有特定的构 型.…”
Section: 手性金属纳米团簇unclassified
“…[ 16 ] For example, Nordlander et al [ 17 ] reported chiral diphosphine modified H 4 Ru 4 nanoclusters for enantioselective hydrogenation of α‐unsaturated carboxylic acids, achieving complete conversion and a 92% ee . Tomishige et al [ 18 ] presented chiral 2‐amino‐2′‐hydroxy‐1,1′‐binaphthyl modified Ir nanoclusters (supported by CeO 2 ) for enantioselective hydrogenation of acetophenone with 99% conversion and 53% ee . In these reactions, the source of active hydrogen (H*) species was hydrophobic molecular hydrogen (H 2 ).…”
Section: Introductionmentioning
confidence: 99%